Effectiveness of Classroom Management at Sekolah Menengah Kejuruan (SMK) in Sulawesi Selatan, Indonesia. - Saleh, Sirajuddin; Haerunisah; Niswaty, Risma; Nasaruddin (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
One indicator that states that teachers (educators) are professional is the ability to manage the class. This study aims to describe the effectiveness of class management in class X students at Vocational high School (Indonesia: Sekolah Menengah Kejuruan / SMK) Country 1 Maros. This research is a quantitative descriptive. The study population was all students of State Senior High School 1 Maros class X, totaling 462 students, because of the large population, this study conducted 10 percent sampling so that a sample of 46 people was obtained. The techniques used in data collection are observation, questionnaires, interviews, and documentation. Data analysis is presented through a frequency table and processed through a score calculation technique. The data analysis technique in this study uses the percentage formula. The results of this study indicate that the effectiveness of class management in class X students at SMK Country 1 Maros has been carried out very effectively with a percentage of 81.54%. These results are seen from three indicators, namely; 1) the physical condition in the very effective category with a percentage of 84.35%, 2) the socio-emotional condition in the very effective category with a percentage of 85.51%, 3) the organizational condition in the effective category with a percentage of 72.90%.